KONSEP KETUHANAN DALAM SUARA GAMELAN MENURUT LONTAR AJI GHURNNITA - I Putu Ariyasa Darmawan; Ida Bagus Wika Krishna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Balinese gamelan art is one of instrument to complete the worship of the God in the yajña ceremony. Lontar Aji Ghur?nita is one of the reference sources of the artist Balinese gamelan in make and serve Balinese gamelan, because Lontar Aji Ghur?nita contains about the history about Balinese gamelan, centain of the value of Hindu theology and purification gamelan, rules, moral, and abstinence for gamelan teachers. Lontar Aji Ghur?nita is a text about karawitan art or gamelan, depicts a knowledge in creating every gamelan and divinity aspects which serve as basic every sound being produced by every lath. The numbers of lath are undeniably the number of Gods and Goddesses which are explained in the manuscript of Aji Ghur?nita, showing that God comes from everything for real, been everywhere, but it is one. The philosophy of divinity inside is explained into the concepts of Catur Loka Phala and Dewata Nawa sanga.